Social optimism as epiphenomenon of subjective assessment of Belarusian students’ life quality - Simkhovich, Valentina A.; Naumau, Dzmitry I. (Journal of the Belarusian State University. Sociology, 2021)
The article is devoted to the subjective assessment of the Belarusian student youth’s life quality, considered in the context of the implementation of the state youth policy. The concept of life quality is considered within the framework of the subjective approach that attributes to the individual a fundamental role in social life. Measuring of the subjective quality means making use of the index method, designed to reduce social information to a single indicator, regardless of the total number of the object’s indicators. Within the framework of the developed technique for measuring life quality, calculated were individual (particular) indices that describe the characteristics of the student youth’s public consciousness to certain aspects of life quality, as well as the integral index of life quality and aggregate index of the standard of living. The indicators of life quality are as follows: subjective assessment of the material standard of living, subjective assessment of health, accessibility and quality of medical care, subjective assessment of accessibility and quality of education, subjective assessment of accessibility and quality of social infrastructure, subjective assessment of the state of ecological environment, subjective assessment of quality of social environment and satisfaction with quality of life. The given technique enables to diagnose various aspects of the students’ life and identify weaknesses in implementing particular areas of the state youth policy. It was used to measure the quality of life of the Belarus State Economic University students who were the object of the study carried out in two stages – in 2019 and 2020. A comparative analysis of the data showed that the respondents demonstrated a high degree of satisfaction with both objective living conditions and subjective perception of the degree of satisfaction with their needs. The analysis of the general indices of subjective quality of life in retrospective, current and prospective aspects testifies to the respondents’ social optimism since their values do not decrease and in some cases increase. The only exception is the value of the index of subjective assessment of social environment quality: its decrease in 2020 indicates that the respondents fixed a negative impact on their lives and life of the whole society, which was caused by the socio-economic consequences of the COVID-19 pandemic and the political crisis in the country. Although social optimism is weakly expressed, the given epiphenomenon can be explained by the fact that the young people consider all indicators of life quality as virtually equal that is both conditioned by the results of socialisation and logic of a modern society’s development.